Common Energy Policy and Mechanisms Aimed at Unification of Legal Regulation Related to Foreign Trade turnover of BRICS Energy Resources - ISHAKOVA, Agnessa O.; MARCHUKOV, Igor P.; SVESTYANOV, Maxim V. (Journal of Advanced Research in Law and Economics, 2017)
The article deals with legal methods and means of unification of legal regulation of foreign trade turnover of energy resources in BRICS, which today presents a powerful, dynamic alliance, committed to new industrial standards, which demonstrates sustainable economic growth and rapidly growing impact on regional and global markets, including energy. We study the factors and general policy measures aimed at strengthening the national security and the economic power of the member countries of BRICS as a whole, contributing to the development of all sectors of the economy, as well as the nature of the event, narrow section, aimed at the development of foreign trade of energy resources. It is proved that the BRICS association promotes global economic positions of Russia and may become one of the most powerful tools of its foreign trade, including in the energy sector. It is concluded that the development of international energy co-operation of Member States BRICS priority jurists favor the creation of a single legal space. As for direct foreign trade of energy resources, the priority must first be given to the harmonization of national civil law, as a branch of law that regulates private-trade relations with a foreign element, the implementation of which requires a call to the harmonization of the law.